Hubungan Pembelajaran Akidah Akhlak Dengan Perkembangan Akhlak Remaja di Solihuddin School, Chana Thailand - Baisa, Hidayah (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2017)
This article discusses the phenomenon of matters of adolescent morality that is very apprehensive in the global era. Teenagers seem to have escaped from the intrinsic values ​​of religion as the benefit of the people’s life. Aqidah akhlaq education has become a curriculum in schools, students are expected to grow and improve their faith; through attitude and praiseworthy behavior. In addition, students are also expected to achieve balance material and spiritual, alignment of the relationship between humans in the social sphere of society and the environment, also especially strengthen human relationships with God. This paper intends to know the relationship of aqidah akhlak with the development of morals in Solihuddin School, Chana Thailand. How is the implementation of moral aids in Solihuddin School Chana Thailand ?; And how is the development of morality in the environment of Solihuddin School Chana, Tahiland? And how is the relationship between the learning of moral character and the development of morals in Solihuddin School Chana Thailand? The research was conducted at Solihuddin School, Chana Thailand. The data obtained through observation, interviews, documentation and questionnaire given to 30 students as sample or 30% of the total population of 103 students. From the research, it can be concluded that the implementation of aqidah akhlak teaching has significant relationship with the development of morality in adolescent at Solihuddin School, Chana Thailand.